Effect of Marketplace Use and Learning Entrepreneurship on Interest in Entrepreneurship Social Science Students at Sma Negeri 6 Oku - Indah Yustika Sari; Risma Margaretha Sinaga; Novia Fitri Istiawati (International Journal of Educational and Life Sciences, 2024)
This research aims to determine the influence of marketplace use and entrepreneurship learning on students' entrepreneurial interest. This research uses an ex post facto and survey approach. The population of this study were students of class XI IPS 1, XI IPS 2, XI IPS 3, SMA Negeri 6 OKU, totaling 105 students. The sample used in this research was 83 students using a probability sampling technique using random samples. Data is collected through questionnaires/questionnaires. Hypothesis testing used in this research is the t and F tests which are processed using the SPSS program. The results of this research prove that the variables of marketplace use and entrepreneurial learning have a good influence. Based on the results of data processing obtained by a partial test, the use of the marketplace on interest obtained a value of 0.124, which proves that every time there is an addition of one unit to the variable of marketplace use (X1) will cause an increase in the variables of interest in entrepreneurship and entrepreneurial learning on interest, a value of 0.645 was obtained, which proves that Every time there is an addition of one unit to the entrepreneurial learning variable (X2) will cause an increase in the entrepreneurial interest variable. Then it was strengthened by simultaneously obtaining test result data, a value of 0.632 was obtained with a determination value of 0.400 or 40% and the remaining 60% was influenced by other variables not examined in this research.